Pattern And Determinants of Health-Related Quality of Life Among Systemic Lupus Erythematosus Patients In Libyan Healthcare Settings - Buni, Halima; Taher Ashur, Sana; Nagi, Boshra (Libyan Journal of Public Health Practices, 2024)
Systemic lupus erythematosus (SLE) is a long-term autoimmune disease affecting multiple systems in the body and is known to cause considerable morbidity and mortality. This study's objective was to evaluate several Health-related Quality of life (HRQoL) dimensions among SLE patients getting treatment in Libyan medical care facilities. Additionally, it examined how certain clinical and socio-demographic variables affect every HRQoL domain. A cross-sectional study was conducted at the Rheumatology Department of the Tripoli University Hospital-Libya during October 2022 and targeted patients with confirmed diagnosis of SLE. Data was collected using a self-reported questionnaire that included the RAND 36-Item Health Survey 1.0 version of the SF-36. The data was analyzed using the SPSS. A total of 50 respondents filled in the questionnaires. The mean age of the participants was 44.79 years (SD=12.31) and 80.0% of them were females. The least impacted HRQoL domains were Physical (mean=72.52, SD=28.04) and Social functioning (mean=66.25, SD=32.26). While the most affected domain was Role limitation due to emotional problems (mean=35.33, SD=41.18). Energy/ Fatigue (p=0.021) and Emotional well-being (p=0.011) scores were significantly higher in males. Physical functioning mean score was significantly higher in unmarried patients (p=0.037). The mean of Role limitation due to emotional problems score(p=0.038) and the Energy/ Fatigue scores were significantly lower in patients with comorbidities (p=0.019). The least impacted HRQoL domains were Physical and Social functioning. While the most affected domain was Role limitation due to emotional problems. The main factors associated with lower HRQoL scores were, female sex, marriage, low monthly income, and presence of comorbidities.